Weed-Species Abundance and Diversity Indices in Relation to Tillage Systems and Fertilization - Travlos, Ilias S.; Cheimona, Nikolina; Roussis, Ioannis; Bilalis, Dimitrios J. (Frontiers in Environmental Science, 2018)
Weeds pose a major threat to world agriculture by reducing detrimentally crop yield and quality. However, at the same time, weeds are major interacting components of the agroecosystems. Abundance and diversity of weeds vary significantly among the several communities. In order to evaluate each community’s structure and the interactions among them, several population indices are used as key tools. In parallel, various cultivation and land management strategies, such as tillage and fertilization, are commonly used in terms of integrated weed management. Estimating the response of weed species on those practices is crucial for both biodiversity maintenance and alternative weed control methods. Many experiments have confirmed the fundamental role of tillage intensity and nutrition supply in weed species’ abundance and diversity. For instance, in some studies, the abundance of perennial weeds was doubled under reduced tillage intensity. In addition, higher values of Shannon-Weiner and Pielou indices were reported in the PK fertilization treatment compared to the control and NK fertilization treatments. The objective of this paper is to provide a brief overview of the key results of these experiments and summarize the part of the literature related to the effect of tillage systems and fertilization on weed species abundance and diversity. Such knowledge could contribute to the sound design and implementation of integrated weed management programs which in turn may lead to a decrease in the density of serious and noxious weeds and an increase in the overall balance of agroecosystems.